Implementasi Kebijakan Tugas Guru Pembimbing Khusus pada Pendidikan Inklusif di SD Negeri se-Kecamatan Junrejo Batu - Indriawati, Prita (Jurnal Kebijakan dan Pengembangan Pendidikan, 2013)
This research focus in implementation policy on Special Supervising Teachers duties based on grant policy Permendiknas No. 70 in 2009 junto Pergub Jatim No. 6 in 2011 pasal 10 ayat 1. This research aims: 1) described the duties of special supervising teachers in the process of identification, assessment service in arranging program of instruction individually on inclusive education in public elementary school Junrejo Batu ; 2 ) described implementation duty Special Supervising Teachers on designing and delivering program specificity on on nclusive education in public elementary school Junrejo Batu; and 3) described implementation duty Special Supervising Teachers in modifying teaching on inclusive education in public elementary school Junrejo Batu. This research use qualitative approach in the form of research policy. Determination respondent used technique purposive sampling. To collect the data used in-depth interview to: 1) the principal of inclusive education in public elementary school Junrejo Batu, 2) special supervising teachers of inclusive education in public elementary school junrejo Batu; 3) shadow teacher of inclusive education in public elementary school Junrejo Batu.